Nurse performance viewed from motivation discipline leadership and environment - Suharmanto Suharmanto; Sudarwati Sudarwati; Istiatin Istiatin (Institute of Computer Science (IOCS), 2023)
Employee performance is very important for a business to be successful and achieve its goals. This research is urgent to do because it provides a better understanding of the factors that influence the performance of nurses at Bung Karno General Hospital, Surakarta. This study aims to determine the effect simultaneously or partially of motivation, discipline, leadership and environmental variables on the performance of nurses at the Bung Karno Regional Public Hospital, Surakarta. This research method uses a quantitative research design. The sample in the study was 80 nurses at the Bung Karno Regional Public Hospital in Surakarta who were taken using a census or saturated sampling technique. Data collection used a questionnaire. The data analysis technique used statistical analysis, namely multiple linear regression test, F test, t-test, and coefficient of determination. The results showed that motivation, discipline, leadership and the environment had a significant effect on the performance of nurses at the Bung Karno Regional Public Hospital in Surakarta, both partially and simultaneously.